Pengaruh Strategi Pembelajaran Ekspositori Terhadap Kemampuan Bercerita Siswa - Rusmiati Rusmiati; Ida Bagus Kade Gunaya; Moh. Irawan Zain (Program Studi Magister Pendidikan IPA, Universitas Mataram, 2022)
This research aims to find out the influence of expository learning strategies on the storytelling ability of students of grade IV SDN 32 Cakranegara. This study is an experimental study to look for the influence of expository learning strategies on storytelling skills. This type of research is a type of quantitative research that is by using Quasi design experiments. The experimental design form used in this study was a nonequivalent control group design. This method of data collection uses tests. This method of data analysis is Descriptive Statistical Analysis which describes the implementation of learning syntax. In the data collection of this study, there are prerequisites for data analysis, namely by conducting data normality tests using the Kolmogorov Smirnov test, homogeneity test using Levene, and hypothesis test using independent sample T-test. The hypothesis results in this study are sig 2-tailed < 0.05 which is 0,000 < 0.05 at a significant level of 0.05 in accordance with the hypothesis testing criteria that sig 2 tailed < 0.05 then the alternative hypothesis (Ha) is accepted while hypothesis zero (H0) is rejected. This means that there is a significant difference in storytelling skills between the students of the experimental group and the control group. Thus, it is stated that expository learning strategies can be applied to improve the storytelling skills of grade IV elementary school students.